Study Of Hemoglobinopathies in Patients of Anemia Using High Performance Liquid Chromatography (HPLC) In Western India - Bhalodia, Jignasa N; Oza, Haren V; Modi, Palak J; Shah, Ami M; Patel, Kinara A; Patel, Himani B (National Journal of Community Medicine, 2015)
Introduction: In India, major cause of anaemia is nutritional deficiencies which can be treated by medications. Hemoglobinopathies are the most common inherited red cell disorders worldwide. Most clinically significant hemoglobinopathies are inherited defects of the beta (β) globin chain of adult haemoglobin. Identification of these disorders is immensely important epidemiologically and for improved management protocols. Our aim is to detect the haemoglobin disorders in patients with anaemia and to assess the suitability of using high performance liquid chromatography (HPLC) routinely for screening patients with anaemia. Methods: A total of 500 cases of patient’s with anaemia having haemoglobin up to 11 gm% were studied for routine haematological investigations and by HPLC for diagnosing any abnormal haemoglobin disorder by BIO RAD ‘VARIANT’ analyser. Results: Out of 500 cases of anaemia studied, 43 cases showed abnormal haemoglobin fractions on HPLC. Of these, 26 cases of the beta Thalassemia trait was the predominant abnormality (5.2%). There were 6 cases of sickle cell trait patients (1.2%), 4cases of high Hb F patients (0.8%) and 2 cases of Hb D Punjab heterozygous patients (0.4%). Other hemoglobinopathies were also identified in smaller proportions. Conclusion: HPLC is very simple, accurate and superior technique in early detection of various haemoglobin disorders, which helps in early management of patients.